PENGELOLAAN ALOKASI DANA DESA DI DESA NUPABOMBA KECAMATAN TANANTOVEA KABUPATEN DONGGALA - Kusumo, Hario Abi (Katalogis, 2016)
This research aims at describing the management of funds allocation at Nupabomba village, Tanantovea district, Donggala regency. This research used qualitative descriptive method. The data were collected through observation, interview, and documentation. The five informans were taken through purposive sampling technique. The result show that the management of funds allocation at Nupabomba village, tanantovea district, Donggala regency was not optimal related to the some aspects that were examined: planning aspect has not reached the expected target, organization and movement aspects have reached the expected target, and the monitoring aspect has not reached the expected target.